Analysis of the Impact of Digitalization of Financial Statements and Internal Control on Report Accuracy and Shareholder Trust in Public Companies in Indonesia - Loso Judijanto; Samsu . G; Deni Iskandar (West Science Social and Humanities Studies, 2024)
This study examines the impact of financial statement digitalization and internal control on report accuracy and shareholder trust in public companies in Indonesia. Employing a quantitative approach with 240 samples, data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings indicate that digitalization significantly enhances shareholder trust by improving the transparency and accessibility of financial information. Internal control emerges as a key factor in ensuring report accuracy, which indirectly strengthens shareholder confidence. The results underscore the need for public companies to integrate digital tools with robust internal controls to achieve high-quality financial reporting and foster stakeholder trust. This study contributes to the theoretical understanding of digitalization and governance while offering practical insights for improving corporate transparency in emerging economies.